Contrasting of CSR Strategies self-presentations and consumers expectations in Serbia - Čurčić, Radmila D; Miletić, Ljiljana Z; Bjegović, Miroslav J (Industrija, 2016)
Corporate social responsibility (CSR), as a widely accepted approach is often applied by the companies not only to create a social impact but also as a powerful tool to create the image of the company among customers and increase its visibility. In order to contrast the CSR concepts of leading companies in Serbia as a country in a long-lasting post-socialist transition with the consumer expectations search of web based self-presentations of leading companies in Serbia and questionnaire among consumers were used in present research. Obtained results point out that self-presentation of CSR programs by the leading companies in Serbia is in collision with consumers expectations in respect to both, presented CSR motives and emphasized CSR activities. Companies are mainly emphasizing performance driven motives for CSR, while consumers rate higher the motives related to stakeholders and value based motives. Environment protection is the only activity recognized with similar importance by the companies and by the consumers. Consumers expectations are highest in respect to stakeholder related CSR including consumers, employees and suppliers, while the companies rarely emphasize these aspects of CSR. Oppositely, support for social issues and donations employed very frequently by the companies do not meet high consumers’ expectations.